2018
DOI: 10.1186/s13104-018-3819-2
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis-related deaths in the at-risk population on the wards: attributable fraction of mortality in a large point-prevalence study

Abstract: ObjectiveSepsis mortality is reported to be high worldwide, however recently the attributable fraction of mortality due to sepsis (AFsepsis) has been questioned. If improvements in treatment options are to be evaluated, it is important to know what proportion of deaths are potentially preventable or modifiable after a sepsis episode. The aim of the study was to establish the fraction of deaths directly related to the sepsis episode on the general wards and emergency departments.Results839 patients were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…In a recent randomised controlled trial of community-acquired sepsis with very similar patient population characteristics to our study, early (within 1-h of recognition) broad spectrum antibiotic administration failed to improve clinical outcomes compared to the usual care group which received antibiotics after assessment in the ED [21]. We have shown, that severe infection leading to organ dysfunction per se is relatively rarely attributable to death in the same patient population [22]. This finding was echoed in a recent study from the US, where Rhee et al found that although sepsis was present in 52% of terminal hospitalisations, underlying causes of death were related to severe chronic comorbidities and most sepsis-associated deaths were unlikely to be preventable through better hospital-based care [23].…”
Section: Discussionmentioning
confidence: 49%
“…In a recent randomised controlled trial of community-acquired sepsis with very similar patient population characteristics to our study, early (within 1-h of recognition) broad spectrum antibiotic administration failed to improve clinical outcomes compared to the usual care group which received antibiotics after assessment in the ED [21]. We have shown, that severe infection leading to organ dysfunction per se is relatively rarely attributable to death in the same patient population [22]. This finding was echoed in a recent study from the US, where Rhee et al found that although sepsis was present in 52% of terminal hospitalisations, underlying causes of death were related to severe chronic comorbidities and most sepsis-associated deaths were unlikely to be preventable through better hospital-based care [23].…”
Section: Discussionmentioning
confidence: 49%
“…However, the repeated nationwide point-prevalence studies in Wales between 2015-2017 have yielded similar results, in incidence of sepsis, bundle compliance and likely cause of death. 7,24,27,28 Similarly, the international IMPRESS study reported similar rates of sepsis outside of critical care and low bundle compliance. 29…”
Section: Discussionmentioning
confidence: 97%
“…It is also noteworthy that, even in non-geriatric settings, only a minority of deaths occurring in patients admitted for sepsis are directly and undoubtedly attributable to the infection [45,46]. The attributable fraction of mortality related to sepsis has been esteemed in 15% of patients admitted to ICUs and 24.1% of patients admitted to non-ICU wards [45,46]. In this scenario, frailty and multimorbidity may play a relevant role in defining the prognostic trajectory, even when an acute, disseminated, and life-threatening infection is present.…”
Section: Discussionmentioning
confidence: 99%